2018
DOI: 10.3390/scipharm86020017
|View full text |Cite
|
Sign up to set email alerts
|

Betulin-3,28-diphosphate as a Component of Combination Cytostatic Drugs for the Treatment of Ehrlich Ascites Carcinoma In Vitro and In Vivo Experiments

Abstract: The activity of betulin-3,28-diphosphate (BDP) in combination with the cytostatics such as 5-fluorouracil (5-FU) and hydrazine sulfate (HS) was demonstrated by using the transplanted Ehrlich ascites carcinoma (EAC) in mice. The dose-dependent effect of combination drugs BDP + HS and BDP + 5-FU was revealed by in vitro experiments on rats. The synergetic effect of HS and BDP on oxidative stress and energy metabolism was established. The malonic dialdehyde (MDA) level both in plasma and erythrocytes decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
7
1
Order By: Relevance
“…In this study, we observed 2 fold decrease in free radicals when treated with SR033 as compared to untreated controls, however, 1.2 fold decrease was observed when compared 5FU alone groups with SR033 + 5FU groups. The effect of SR033 in combination to 5FU showed comparable results to abovementioned reports (56,57). While the data does show that SR033 alone significantly reduces the number of free radicals, the practical application of using SR033 alone to treat cancer is not feasible (58).Similar studies were also performed earlier (59,60).…”
Section: Sr033 Increases Sod In Hela and Hela-r Cellssupporting
confidence: 75%
See 2 more Smart Citations
“…In this study, we observed 2 fold decrease in free radicals when treated with SR033 as compared to untreated controls, however, 1.2 fold decrease was observed when compared 5FU alone groups with SR033 + 5FU groups. The effect of SR033 in combination to 5FU showed comparable results to abovementioned reports (56,57). While the data does show that SR033 alone significantly reduces the number of free radicals, the practical application of using SR033 alone to treat cancer is not feasible (58).Similar studies were also performed earlier (59,60).…”
Section: Sr033 Increases Sod In Hela and Hela-r Cellssupporting
confidence: 75%
“…Treatment of HeLa-R cells at IC50 values of HeLa cells in the combination of SR033 (600 μg/mL) with 5FU (2 μg/mL) and PTX (5.96×10 -3 μg/mL) resulted in 80% and 88% death of HeLa-R, treated with SR033 + 5FU, hence displaying its antioxidant capability. However, in earlier reports, use of 5FU with Irinotecan resulted in a 3 fold decrease in free radicals (56), whereas no significant increase was observed withbetulin-3, 28-diphosphate (57). In this study, we observed 2 fold decrease in free radicals when treated with SR033 as compared to untreated controls, however, 1.2 fold decrease was observed when compared 5FU alone groups with SR033 + 5FU groups.…”
Section: Sr033 Increases Sod In Hela and Hela-r Cellscontrasting
confidence: 69%
See 1 more Smart Citation
“…In addition to improved solubility, betulin phosphates and phosphonates showed high activity as potential drugs [18][19][20][21][22][23]. In vitro and in vivo experiments demonstrated antimicrobial [19], antifungal [20], anti-inflammatory, antiviral [21] activities and an antitumor effect in the treatment of ductal carcinoma, glioblastoma, melanoma [22], Ehrlich ascites carcinoma [23] and other diseases.…”
Section: Fig 1: Formulas Of Salt Complexes Componentsmentioning
confidence: 99%
“…Triterpenoids are able to potentiate the 5-fluorouracil effect by affecting different stages of esophageal carcinoma and other tumors [8,9]. Previously, we showed the animals state improvement indicated by survival, body weight, wool, behavior, reduced cardiotoxicity when Ehrlich carcinoma was treated by the combination of 5-fluorouracil or hydrazine sulfate with betulin-3,28-diphosphate in in vivo experiment [10]. The effect may be due to the decreased dose of high toxic cytostatics and increased metabolic processes in an animal body, including antioxidant enzyme protection and energy metabolism activation.…”
Section: Introductionmentioning
confidence: 97%